PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA RUMAH SAKIT SARILA HUSADA SRAGEN) - Visiana Kusma Warjana; Khabib Alia Akhmad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance at Sarila Husada Hospital Sragen. This research employed a quantitative approach using a survey method. The population consisted of employees of Sarila Husada Hospital Sragen, with a sample of 57 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS), including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²). The results indicate that leadership style has no significant effect on employee performance, while work motivation has a positive and significant effect on employee performance. Simultaneously, leadership style and work motivation have a significant effect on employee performance. The coefficient of determination (Adjusted R Square) shows that the independent variables explain 49.4% of the variation in employee performance, while the remaining 50.6% is influenced by other variables outside this study. The findings are expected to serve as a reference for hospital management in improving employee performance through strengthening work motivation and implementing more effective leadership.